Environmental factors and health : (Danish Environmental Protection Agency, 2001)
This book consists of the following many parts such as basic information about Denmark, environmental factors with possible health implications, the regulatory framework, a historycal overview of environmental policy in Denmark, air, soil, drinking water, bathing water-coastal and fresh-waters....